2016
DOI: 10.1590/1806-9061-2015-0070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kluyveromyces marxianus Isolated from Tibetan Mushrooms on the Plasma Lipids, Egg Cholesterol Level, Egg Quality and Intestinal Health of Laying Hens

Abstract: The effects of the Kluyveromyces marxianus M3 strain, isolated from Tibetan mushrooms, on plasma lipids, egg cholesterol level, egg quality, and intestinal health of laying hens were evaluated. In total, 160 Beijing fatty laying hens (43 weeks old) were divided into four groups and fed a basal diet supplemented with 0%, 0.1%, 0.3%, or 0.5% freeze-dried K. marxianus M3 powder for four weeks. The results showed that yeast supplementation reduced serum total cholesterol (TC), triglyceride (TG), low density lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
3
3
0
Order By: Relevance
“…The highest egg weight was observed in hens fed 0.1 and 0.2% yeast culture during the experimental period, and this difference was statistically significant (P<0.05). Our findings corroborate previous studies (Ayanvale et al, 2006;Yalçin et al, 2008;Yalçın et al, 2015;Zhong et al, 2016), but disagree with others (Nursoy et al, 2004;Asli et al, 2007;Hassanein and Soliman, 2010;Gül et al, 2013;Sacakli et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The highest egg weight was observed in hens fed 0.1 and 0.2% yeast culture during the experimental period, and this difference was statistically significant (P<0.05). Our findings corroborate previous studies (Ayanvale et al, 2006;Yalçin et al, 2008;Yalçın et al, 2015;Zhong et al, 2016), but disagree with others (Nursoy et al, 2004;Asli et al, 2007;Hassanein and Soliman, 2010;Gül et al, 2013;Sacakli et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…The best Haugh unit was found in the third trial group (P<0.005). Similarly, previous studies (Ayanwale et al, 2006;Yousefi and Karkoodi, 2007;Asli et al, 2007;Zhong et al, 2016) reported that egg yolk weight was increased by the supplementation of yeast culture.…”
Section: Discussionsupporting
confidence: 65%
“…It has traditionally been considered a dairy yeast but whole genome comparisons and studies of Lac12p variation showed that only a subset of K. marxianus strains are adapted to this niche (Ortiz-Merino et al, 2018). Examination of the origins of K. marxianus strains in culture collections shows that the yeast can be isolated from plants, fruits and other non-dairy niches plant sources (Suzuki et al, 2014; Zhong et al, 2016). It can be speculated that the expansion and functional diversification of MFS sugar transporters has its origins in pressures in the evolutionary history of K. marxianus.…”
Section: Discussionmentioning
confidence: 99%
“…Kalsum et al (2012) reported that single probiotic of L. fermentum lowered cholesterol content in egg yolk. The reduction effect of the cholesterol content of the eggs by more than 26% was reported by using Kluyveromyces marxianus M3 strain yeast (Zhong et al, 2016). Khalifa and Noseer (2019) reported that quail fed on combination of probiotics (L. acidophilus, 10 6 cfu and S. cerevisiae 10 2 cfu) with ginger produced the lowest yolk cholesterol (10.6 mg/g) compared to control group (14.1 mg/g).…”
Section: Cholesterol Content In Egg and Meatmentioning
confidence: 98%
“…Manafi et al (2016) stated that the dietary inclusion of B. subtilis and BMD were not effecting the eggshell characteristics i.e., thickness, breaking strength, percentages, and also haugh unit. Zhong et al (2016) stated that supplementation of 0.3% yeast Kluyveromyces marxianus M3 strain on laying hen diet resulted in significant differences in the eggs nutrient composition (increase protein, crude fat level, and dry matter), weights, shell strength, albumen height, and haugh unit. Siadati et al (2018) reported that probiotic treatments (Protexin, Primalac, and Lactobacillus strains) had significant positive effects (P<0.05) on the height of albumen, haugh unit, and internal quality unit (IQU), whereas eggshell, yolk weight, and egg albumen weight of the quails were not affected by the treatments (P>0.05).…”
Section: Quality Of Quail Eggsmentioning
confidence: 99%